Potential for Fiscal Decentralization in the Public Sector of the Republic of Bulgaria - Dzhinsov, Stanislav (Research Papers, 2025)
Fiscal decentralization is increasingly establishing its importance as a key element in the effective redistribution of public goods. It is an undeniable fact that this process not only stimulates the development of individual institutional agents within the vertical structure of the public sector, but also contributes to sustainability in long-term planning and budgeting. Decentralization, in its essence as a governance model and structure, provides a powerful tool for transferring resources and responsibilities from central to local authorities, enabling greater economic, political, and social independence in local self-governance.